The Effect of KPRS Akad Selection on the Profitability of Bank Jatim Syari'ah Kediri Branch - Sutantri, Sutantri; Mala, Iva Khoiril; Ma'rifah, Selah Nurul (Program Pascasarjana STIE Amkop Makassar, 2023)
One of the most productive financing products is KPR Syari'ah. The KPRS application at BJS Kediri uses two contracts, namely Murabahah and Musyarakah Mutanaqishah (MMQ). The difference in contracts causes different performance results for KPRS, especially in terms of profitability. Then, which contract has the potential to be more profitable for BJS Kediri? This research is a descriptive quantitative research. The sample is 28 from the performance and financial statements for the period 2016–2022. Data collection using documentation, observation and interview techniques. The data processing and analysis techniques used are the Coefficient of Determination Test and Moderated Regression Analysis (MRA) with the help of SPSS 29.0 Software for Window. The results showed that the contract that affects the profitability of BJS is MMQ, while the Murabahah contract. Then, NPF only moderated the effect of Murabahah on BJS Profitability and not on MMQ. Researchers concluded that the KPRS contract that is more profitable for BJS is MMQ, but it still requires more attention in several aspects such as promotion and recording system.